In-Vehicle Monitoring by Radar: A Review - Gharamohammadi, Ali; Khajepour, Amir; Shaker, George (IEEE sensors journal, 2023)
The proliferation of vehicles and a subsequent increase in traffic accidents have led to a heightened focus on driving safety. As a result, various researchers have been examining ways to enhance driving safety in daily life by implementing smart car technology. In-vehicle sensing utilizing radar technology has emerged as a leading method for monitoring the driver's health, emotions, and attention, owing to its numerous advantages over traditional sensors, including the ability to detect subjects through nonmetallic surfaces and the inherent privacy-preserving mechanisms. In recent years, in-vehicle sensing through radar has undergone significant advancements. This article aims to provide a comprehensive survey of the applications, system-level design, and signal processing of in-vehicle sensing through radar. The published works in this field are categorized into three main groups: occupancy detection, gesture recognition, and occupant status monitoring. This article will discuss the highlighted works and their respective advantages and limitations in terms of applications.